The Lasater Clinical Judgment Rubric as a Framework to Enhance Clinical Judgment in Novice and Experienced Nurses. Issue 5 (September 2015) - Miraglia, Robbin; Asselin, Marilyn E.
<x xml:space="preserve">Abstract</x> Clinical judgment has been identified as a critical component of professional nursing practice and enables nurses to deliver safe patient care with optimal outcomes. Nurses, particularly those transitioning into clinical practice, may require assistance to enhance their clinical judgment skills. This article presents the Lasater Clinical Judgment Rubric, which has primarily been used in the academic setting, as a framework for nursing professional development specialists to enhance the clinical judgment skills of novice and experienced nurses.